SYSTEM OF STATE INSURANCE PRINCIPLES: CHARACTERISTICS OF THE CONTENT AND ELEMENTAL COMPOSITION - FEDORIUK, LUDMYLA (Ehrlich’s Journal, 2024)
The article analyses the system of principles of state insurance as a system of initial normative and guiding ideas on the basis of which state social insurance is implemented. It is established that the principles of social insurance delineate social standards, establish clear guidelines, and chart paths for the development of normative legal regulation of socio-economic relations arising in connection with the social protection of the population from the consequences of social risks. The system of principles of state insurance characterized as an organized set of principles that guarantee the financial security of citizens in the event of an insured event, as well as the provision of social services funded by the budget of the social insurance fund. It is established that the system of principles of state insurance includes the following elements: legality of social insurance; state guarantee of social insurance; ensuring a decent level of socio-economic conditions for the insured person; compulsory social insurance; equality of social insurance – all insured individuals contribute funds and subsequently receive rights and guarantees of uniform provision of social assistance and social protection against specific insurance risks; social partnership in social insurance; solidarity of social insurance. It is emphasized that the system of principles of state insurance forms a system of guiding ideas and guiding principles. These principles carry significant cognitive weight, allowing for the comprehension of various processes in social security. From a practical standpoint, they serve as a kind of general norms, which, when used correctly, become a sufficient precondition for constructing a state policy strategy in the field of state insurance.